Batavia in Crisis: Disease Outbreaks and Public Health Responses in the 20th Century - Aditiya, Wisnu Rega; Susilowati, Endang; Yuliati, Dewi (Jurnal Sejarah Citra Lekha, 2024)
This study investigates the health crisis that gripped Batavia during the early 20th century, characterized by recurrent disease outbreaks. The development of the outbreak was influenced, among other by the unhealthy lifestyle of the population, the lack of knowledge regarding handling existing outbreaks, as well as climate and weather factors in the Batavia region which supported the spread of the disease. By examining the interplay of socio-economic conditions, public health practices, and environmental factors, this research seeks to elucidate the factors contributing to these epidemics. Employing a historical methodology,the study analyzes primary and secondary sources to reconstruct the city's health landscape. Findings reveal that Batavia's inadequate public health infrastructure, coupled with poor living conditions, exacerbated the spread of diseases. The city's government struggled to implement effective control measures, leading to significant mortality rates. However, the introduction of mass vaccination programs in the 1910s and 1920s marked a turning point, demonstrating the potential of public health interventions in mitigating disease outbreaks. This research underscores the importance of robust public health systems in preventing and responding to epidemics, a lesson that remains relevant today.